Poor health-related quality of life in the Swedish general population: The association with disease and lifestyle factors. Issue 7 (November 2013) - Djärv, Therese; Wikman, Anna; Johar, Asif; Lagergren, Pernilla
Aim : Poor health-related quality of life (HRQoL) is associated with increased use of healthcare services, but it remains unclear which individuals have a heightened risk in the general population. Methods : A Swedish population-based cross-sectional survey was conducted in 2008. Predefined risk characteristics including sex, age, educational level, marital status, body mass index, diseases, physical activity, and tobacco smoking were collected by a self-report questionnaire. Five aspects of the EORTC QLQ-C30 were used to assess HRQoL: physical, role, emotional, social, and cognitive function. Participants were defined as having "poor HRQoL" if they scored ≥10 points (scale 0–100) lower than the mean score of the total sample. To assess the characteristics of individuals with poor HRQoL, classification and regression tree (CART) analysis was performed. Results : A total of 4910 (70.5% participation rate) randomly selected individuals participated in the study. The CART analysis showed that for each of the five functional aspects of HRQoL, the most important covariate HRQoL was the number of reported diseases, while the second strongest covariate was physical inactivity. Conclusion : This large population-based study indicates that a higher number of diseases and physical inactivity are the most important covariates of poor HRQoL in the Swedish general population.